Students’ Strategic Thinking Ability Enhancement in Applying Scratch for Arduino of Block Programming in Computational Physics Lecture - Umi Pratiwi; Dwi Nanto (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2019)
As newbie programmers, university students are not accustomed to computer coding. It difficult to solve programming problems especially related to physics phenomena. They need strategic thinking ability to solve problems. Therefore, computational physics subject/lesson applies learning of Scratch for Arduino on block programming in order to enhance students' strategic thinking. This attempt is examined by a study using a quasi-experimental method pre-experimental design approach which is one group pretest-posttest design using third-year physics education students 2018/2019 as the sample. The result shows that students happened to increase their strategic thinking up to 11.7%, particularly on the ability to prove the chosen solution it is appropriate to students' problems in finishing projects categorized as “very good.” It enables them to finish simple physics cases by using Arduino programming and improve their coding ability significantly.